Compressive behavior and stress-strain model of square confined ambient-cured fly ash and slag-based geopolymer concrete. (December 2022) - Du, D.F.; Wang, J.H.; Wang, X.; Su, C.
Abstract: Although a great deal of work has been completed towards the study on geopolymer concrete (GC), most of the efforts have focused on the material mechanical behavior. The objective of this paper is to present the results of an experimental study aimed to investigate the stress-strain behavior of confined fly ash and slag-based GC (FASGC) through the compression testing of a total of fourteen square ambient-cured short columns. The experimental results indicated that the increase in the slag content resulted in higher unconfined compressive strength but more obvious brittle property of confined FASGC. The effectiveness of lateral steel confinement was higher for FASGC than that for ordinary Portland cement-based concrete (OPCC), despite the lateral confinement index K n of the former one was a little smaller compared to the latter one, the maximum differences in both f cc / f c0 and ε cc / ε c0 between them were 20.8% and 59.3%, respectively. Both f cc / f c0 and ε cc / ε c0 were not strongly related to the variation of the spacing of transverse reinforcement. The increase in the diameter of transverse reinforcement was not obviously improve the f cc / f c0 but resulted in the increase in the ε cc / ε c0, nonetheless, the ε cc / ε c0 was only increased by 70.9% as the K n increased 3 times. The models were proposed to predict both ultimate stress and strain and to describe the stress-strain behavior of FASGC with good accuracy, more test data is further need to refine the proposed models. In light of the results, it is recommended to further investigate the effect of the fibers such as steel fiber, FRP fiber on the improvement of the brittle behavior of FASGC.